The role of onco-aesthetic in breast cancer: a clinical report study - Gomes de Oliveira, Tiago; Lima, Áurea (Aesthetic Medicine, 2023)
Background: Cancer, particularly breast cancer, may be associated with a premature aging phenotype. Breast cancer patients have increased risk for depressive syndrome, anxiety disorders and low self-esteem. Aesthetic medicine procedures, particularly regarding facial rejuvenation, have been used in breast cancer survivors showing to be safe and effective, as well as important factors to increase cancer patients quality of life. Aims: To evaluate the impact of a hyaluronic acid (HA) hydration protocol on the skin properties and characteristics, reduction of fine lines, wrinkles, and acne scars of a breast cancer patient under active surveillance. To determine the impact of the results achieved on the patient’s self-esteem. Methods: The developed HA hydration protocol included four fortnightly sessions and two subsequent monthly sessions. In each session, 3 mL of NCTF® 135 HA was injected in papillary dermis, on the middle and lower third of the face, through cannula vectorization; prior treatment photographs were taken; and a skin evaluation by Multi Skin Test Center MC 900® was made. The Rosenberg Self-Esteem Scale was applied at the beginning and at the end of the study. Results: Data revealed an increase of skin hydration (+41%) and of elasticity (+28%); an increase of skin homogeneity, reducing fine lines, wrinkles, and acne scars. Rosenberg Self-Esteem Scale showed equal pre- and post-protocol scores. Discussion: Breast cancer patients under active surveillance can benefit from aesthetic medicine procedures; cannula vectorization may be an alternative to juxta-periosteal procedures. The developed HA hydration protocol demonstrated to improve skin properties and characteristics, increasing skin hydration and elasticity, reducing signs of skin aging, restoring luminosity and homogeneity to the skin. Self-esteem assessment can be a useful tool to evaluate the impact of aesthetic procedures on mental health, particularly in onco-aesthetic.